Legal Analysis of Foreign Nationals in Fiduciary Guarantees: Between Banking Risks and Legal Vacuum - Christanty Leony Sutanto; Djumikasih; Yenny Eta Widyanti (NEGREI: Academic Journal of Law and Governance, 2025)
This study aims to analyze legal certainty for Foreign Nationals (FN) as debtors and creditors in loan agreements with Fiduciary assignments in Indonesia. The background of this research is based on the ambiguity of regulations regarding the legal status of FN in the Fiduciary assignment system, which has the potential to create legal uncertainty for banking institutions and related parties. The applicable regulations, including the Fiduciary Assignment Law and Bank Indonesia Regulations, do not explicitly regulate the authority of FN as fiduciary grantors or fiduciary recipients, leading to various legal interpretations in practice. This research employs a normative juridical method using a statute approach and a conceptual approach. The legal materials used consist of primary legal sources, such as laws and relevant regulations, as well as secondary legal materials from various legal literature. The analysis technique used is systematic and grammatical interpretation to examine the interrelation of norms within the Indonesian legal system. The research findings indicate that although existing regulations limit the role of FNs in certain financial transactions, there are legal loopholes that allow them to be involved in Fiduciary assignments, either as debtors or creditors. This uncertainty poses risks to banking institutions if FN debtors default on their obligations.